2023
DOI: 10.1109/jphotov.2022.3227624
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Silicon Surface Passivation by Negatively Charged Hafnium Oxide Thin Films

Abstract: We have studied the mechanisms underpinning effective surface passivation of silicon with hafnium oxide (HfO 2 ) thin films grown via atomic layer deposition (ALD). Plasma-enhanced ALD with O 2 plasma and a tetrakis(dimethylamido)hafnium precursor was used to deposit 12 nm thick HfO 2 films at 200 °C on high-lifetime 5 Ωcm n-type Czochralski silicon wafers. The passivation was activated by postdeposition annealing, with 30 min in air at 475 °C found to be the most effective. High-resolution grazing incidence X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 39 publications
3
21
0
Order By: Relevance
“…Earlier studies into HfO 2 passivation stated that for HfO 2 -based layers to be incorporated into photovoltaic processing schemes, the temperatures they were exposed to could not exceed 400 °C. 16 We have since shown that HfO 2 -based films perform well up to ∼500 °C, 30 but, nevertheless 400–500 °C temperature range provides a useful benchmark for testing thermal stability.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Earlier studies into HfO 2 passivation stated that for HfO 2 -based layers to be incorporated into photovoltaic processing schemes, the temperatures they were exposed to could not exceed 400 °C. 16 We have since shown that HfO 2 -based films perform well up to ∼500 °C, 30 but, nevertheless 400–500 °C temperature range provides a useful benchmark for testing thermal stability.…”
Section: Resultsmentioning
confidence: 99%
“…The passivation quality of both HfO 2 and Al 2 O 3 are known to be dependent on annealing temperature, with optimal passivation achieved in both cases on annealing at 450-500 °C. 11,30 Photoconductance decay lifetime curves for the three structures activated at 450 °C are shown in Fig. 1(a).…”
Section: Stacks Involving Ultra-thin (1 Nm) Hfo 2 Interlayersmentioning
confidence: 99%
See 3 more Smart Citations